Increased frequencies of circulating and tumor-resident Vδ1+ T cells in patients with diffuse large B-cell lymphoma. Issue 1 (2nd January 2018) - Reboursiere, Emilie; Gac, Anne-Claire; Garnier, Anthony; Salaun, Véronique; Reman, Oumedaly; Pham, Anne-Dominique; Cabrera, Quentin; Khoy, Kathy; Vilque, Jean-Pierre; Fruchart, Christophe; Chantepie, Sylvain; Johnson-Ansah, Hyacinthe; et al.
Abstract: Gamma-delta (γδ) T cells contribute to the innate immune response against cancer. In samples of 20 patients upon DLBCL diagnosis, we found that Vδ1 + T cells were the major γδ T cell subset in tumors and PBMCs of patients, while Vδ2 T cells were preponderant in PBMCs of healthy subjects. Interestingly, the germinal center (GC) subtype was associated with an increase in Vδ1 + T cells in tumors, whereas the non-GC subtype was associated with a lower frequency of γδ T cells. While circulating Vδ1 + T cells of patients or HSs mostly exhibited a naïve phenotype, the majority of tumor Vδ1 + T cells showed a central memory phenotype. Resident or circulating γδ T cells from patients were not functionally impaired since they produced high levels of IFN-γ. Collectively, our findings are in favor of γδ T cell activation in tumors and open new perspectives for their modulation in DLBCL immunotherapy.